Computational prediction and characterisation of ubiquitously expressed new splice variant of Prkaca gene in mouse. (26th March 2013) - Banday, Abdul Rouf; Azim, Shafquat; Hussain, Mohammed Aamir; Nehar, Shamshun; Tabish, Mohammad
Abstract: Prkaca gene of mouse encodes for a cAMP dependent protein kinase catalytic alpha subunit. PKA occurs naturally as a 4‐membered structure having two regulatory (R) and two catalytic (C) subunits each encoded by separate gene. Alternatively spliced two transcript variants are known for the Prkaca gene, which encode for two isoforms of PKA C‐subunits, namely Cα1 and Cα2. These isoforms arise as a result of alternative splicing of the first coding exon with the internal exons. We have identified a new transcript variant using combinatorial approach of bioinformatics and molecular biology techniques involving RT‐PCR, semi‐nested PCR and sequencing. The new transcript variant encoding Cα3 isoform has N‐terminus that differs from Cα1 and Cα2 isoforms. Cα3 isoform also arise as a result of alternative splicing of first coding exon with the internal exon. Newly identified transcript is expressed ubiquitously in different tissues examined.